MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA KATOLIK MELALUI METODE DISKUSI KELOMPOK BERBANTU AUDIOVISUAL BAGI SISWA KELAS V SDK SANTO BERNARDUS MADIUN - Gia Cinta Gumilang Sari; Ola Rongan Wilhelmus (Bahasa Indonesia, 2017)
Gia Cinta Gumilang Sari “Improving the PAK Learning Outcomes through Group Discussion Method using Audiovisual Learning process for Grade V Elementary School of St. Bernardus in Madiun City”. Religious education teaching at Catholic Elementary School aimed to enable each student to build a more faithful Christian life. To build a faithful Christian life means to strengthen Christian faith and to integrate the Gospel of Jesus Christ in daily life of Christian faithful. The application of conventional teaching methods in the learning process is no longer appropriate to the situation of today's learning process. It is because this method is more teacher-centered, and the teachers is playing too much active role in the learning process rather then students. Students just sit, listen, record and memorize whatever taught by teacher. As an effort to improve active involvement of students in teaching and learning process, the researcher feels need to apply a Learning Group Discussion Method using audiovisual learning process while teaching the subjects related to Jesus Christ and his incarnation, especially about the "Death and the Resurection of Jesus Christ. This Research Method is a Classroom Action Research. The term classroom action research is used to emphasize the class as a main setting of study. Classroom action research emphasizes on teacher's skills and techniques as to gain a more qualified information both to improve of learning process and student learning outcomes.